Nutrient conditions affect antimicrobial pharmacodynamics in Pseudomonas aeruginosa - Maik Kok; Thomas Hankemeier; J. G. Coen van Hasselt (Microbiology Spectrum)
ABSTRACT The infectious microenvironment in chronic respiratory tract infections is characterized by substantial variability in nutrient conditions, which may impact colonization and treatment response of pathogens. Metabolic adaptation of the cystic fibrosis (CF)-associated pathogen Pseudomonas aeruginosa has been shown to lead to changes in antibiotic sensitivity. The impact of specific nutrients on the response to antibiotics is, however, poorly characterized. Here, we investigated how different carbon sources impact the antimicrobial pharmacodynamic responses in P. aeruginosa. We evaluated the effect of six antibiotics (aztreonam, ceftazidime, ciprofloxacin, colistin, imipenem, and tobramycin) on P. aeruginosa cultured in a basal medium enriched for seven different carbon sources (alanine, arginine, aspartate, glucose, glutamate, lactate, and proline). Pharmacodynamic responses were characterized by measuring time-kill profiles for a bioluminescent P. aeruginosa PAO1 Xen41 strain. We show that single-nutrient modifications minimally affected bacterial growth rate. For specific nutrient-antibiotic combinations, we find relevant alterations in antibiotic sensitivity (i.e., EC50) and the maximum drug effect (Emax), in particular for ciprofloxacin, colistin, imipenem, and tobramycin. The most pronounced effect was observed for tobramycin, where glucose was found to reduce the EC50 (0.5-fold), whereas lactate-enriched conditions led to a 4.3-fold increase in EC50. Using pharmacokinetic-pharmacodynamic simulations, we illustrate that the magnitude of the nutrient-driven pharmacodynamic changes impact treatment for clinical dosing strategies of tobramycin. In summary, this study underscores the impact of nutrient composition on antimicrobial pharmacodynamics, which could potentially contribute to observed variability of antimicrobial treatment responses in CF patients.IMPORTANCEChronic respiratory tract infections in cystic fibrosis patients present significant challenges for antibiotic treatment due to the complexity of the respiratory environment. This study investigated how variations in nutrient levels, altered during chronic infections, affect pathogen response to antibiotics in an experimental setting. By simulating different nutrient conditions, we aimed to uncover interactions between nutrient availability and antibiotic sensitivity. Our findings provide critical insights that could lead to more effective treatment strategies for managing chronic respiratory tract infections in cystic fibrosis patients while also guiding future research in improving treatment methodologies.